Napping Habit and Risk Factors for Cardiovascular Disease: Does It Matter if It Is Sunday? - Inazumi, Cristina Kano; Andrechuk, Carla Renata Silva; São-João, Thaís Moreira; Cornélio, Marilia Estevam; Rodrigues, Roberta Cunha Matheus; Ceolim, Maria Filomena (Sleep Science, 2025)
To assess the relationships involving the habit of napping and the risk factors for cardiovascular diseases.We conducted a cross-sectional study with 563 participants (mean age: 45.0 ± 8.5 years; 56.7% of female subjects). The variables assessed were sociodemographic characteristics, lifestyle and health habits, clinical variables, and napping habits (intentionality and allocation on weekdays or on weekends). The statistical tests used were the Mann-Whitney and Kruskal-Wallis tests followed by Dunn's post-hoc test and Pearson's Chi-squared. Modified multiple Poisson regression models and multiple linear regression models were adjusted.In total, 56.6% of the participants napped (43.2% during the week and 51.8% on weekends). Unintentional napping predominated on weekdays (22.6%), and intentional napping on weekends (29.7%). Those who intentionally napped on weekdays presented higher serum lipid profile values; those who napped unintentionally on weekdays or on weekends presented higher glycated hemoglobin (HbA1c) values. Age, education, race, marital status, alcohol consumption, and physical activity were associated with increased body mass index (BMI), HbA1c, total cholesterol, high-density lipoprotein (HDL) and non-HDL cholesterol, and triglycerides. Intentional and unintentional napping remained independent risk factors for increased HbA1c and lipid profile.Naps can represent a warning sign for health professionals to start or maintain an individual's follow-up. The present study contributes to the literature by identifying that the habit of intentional napping, especially on weekdays, is associated with changes in the lipid profile.
Keywords: sleep; cardiovascular diseases; excessive daytime sleepiness